Harnessing adult neurogenesis by cracking the epigenetic code. (January 2012) - Jiang, Yindi; Hsieh, Jenny
The adult brain contains a reservoir of neural stem cells (NSCs) that generates functional neurons in a process called adult neurogenesis. Integration of new neurons into mature neural circuits maintains brain tissue homeostasis essential for learning, olfaction and behavior. Even subtle disruptions in NSC self-renewal/differentiation can result in substantial changes in neuronal production rates, contributing to neuropsychiatric symptoms, cognitive dysfunction and epilepsy. Recent studies have revealed pivotal roles for epigenetic regulators of gene expression. Epigenetic and genetic regulation allows a rich array of possibilities to fine-tune neuronal gene expression and offers potential therapeutic opportunities to modulate brain function related to adult neurogenesis. Here we discuss the role of epigenetic mechanisms underlying NSC fate and translational strategies for the future.